Material removal rate of zirconia in electro discharge micromachining - Asfana, Banu; Ali, Mohammad Yeakub; Mohamed, Abd. Rahman; Wayne, N. P. Hung (Trans Tech Publications, Switzerland, 2015)
This paper investigates the material removal rate (MRR) in electro discharge micromachining (micro-EDM) of zirconia. Experimental investigation is carried out with 800 μm diameter tungsten electrode with two varying parameters rotational speed and gap voltage. The MRR data are analyzed and an empirical model is developed using Design Expert software. The optimum parameters for maximum MRR are found to be 375 rpm rotational speed and 80 V gap voltage.